Personality and Party Ideology Among Politicians. A Closer Look at Political Elites From Canada and Belgium - Joly, Jeroen K.; Hofmans, Joeri; Loewen, Peter (Frontiers in Psychology, 2018)
We examined the relationship between Big Five personality and the political ideology of elected politicians. To this end, we studied 303 politicians from Flanders, Wallonia, and Canada, relating their self-reported Big Five scores to a partisanship-based measure of political ideology. Our findings show that, in line with the congruency model of personality, Openness to Experience is the best and most consistent correlate of political ideology, with politicians high on Openness to Experience being more likely to be found among the more progressive left-wing political parties.